MdGRF11, an apple 14-3-3 protein, acts as a positive regulator of drought and salt tolerance. (November 2019) - Ren, Yi-Ran; Yang, Yu-Ying; Zhang, Rui; You, Chun-Xiang; Zhao, Qiang; Hao, Yu-Jin
Highlights: PEG 6000, NaCl, ABA and low temperature (4 °C) can induce the expression of MdGRF11 . Ectopic expression of MdGRF11 improves salt and drought tolerance. Overexpression of MdGRF11 alleviates ROS accumulation. MdGRF11 can interact with MdAREB/ABF transcription factors. Abstract: The 14-3-3 proteins are a family of highly conserved phosphoserine-binding proteins that participate in the regulation of diverse physiological and developmental processes. In this research, twenty 14-3-3 genes in apples, which contained a highly conserved 14-3-3 domain, were identified and divided into two subgroups. Among them, MdGRF11 was further cloned and investigated. qRT-PCR analyses and GUS staining show that MdGRF11 is expressed in various organs and tissues with the highest expression levels found in the fruit. MdGRF11 was upregulated by polyethylene glycol 6000 (PEG 6000), NaCl, abscisic acid (ABA) and low temperature (4 °C) treatments. MdGRF11 -overexpressing transgenic Arabidopsis and apple calli exhibited reduced sensitivity to salt and PEG 6000 treatments. Moreover, the ectopic expression of MdGRF11 improved the tolerance of transgenic tobacco to salt and drought stresses, which grew longer roots, underwent more growth, and presented higher chlorophyll levels than the wild-type control under salt and drought stress conditions. Furthermore, MdGRF11 expression remarkably reduced electrolyte leakage, malondialdehyde content levels, H2 O2 and O2- accumulation under salt and drought stress conditions, which relied on the regulation of ROS-scavenging signaling to reduce oxidative damage of cells after salt and drought stress treatment. MdGRF11 also enhanced tolerance to stress by upregulating expression levels of ROS-scavenging and stress-related genes, especially improving responses to drought stress by modifying the water loss rates and stomatal aperture. Moreover, MdGRF11 could interact with MdAREB/ABF transcription factors through yeast two hybrid analyses. In conclusion, our results indicate that MdGRF11 acts as a positive regulator of salt and drought stress responses through regulating ROS scavenging and other signaling systems.